(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Background: Human dirofilariasis is a larval helminthiasis, and there has been an increase in its incidence in recent years, possibly due to global warmth, urbanization, and increased numbers of stray animals and their migration between settlements. Purpose: To review the clinical features of ocular dirofilariasis in patients treated for the disease at the Filatov Institute of Eye Diseases and Tissue Therapy over 2006-2022. Material and Methods: Medical records of 58 patients treated for dirofilariasis at the Filatov institute in 2006-2022 were retrospectively reviewed. Of these patients, 13 (22.4%) were males and 45 (77.6%) were females, and mean age was 48.8 ± 15.2 years. They underwent a routine eye examination. In addition, they underwent an ocular and orbital ultrasound, computed tomography (CT) or magnetic resonance imaging (MRI). The disease was treated by worm extraction surgery in all patients. The worm was verified at Parasitological Laboratory, and the capsule formed around the parasite was examined at Pathomorphology Laboratory of the institute. Statistics 7 software (StatSoft, Tulsa, OK) was used for statistical analysis. Data are presented as mean plus or minus standard deviation. Student t test was used for data comparison. The level of significance р ≤ 0.05 was assumed. Results: Patients treated were most commonly from the city of Odesa and Odesa region (25.9% or 15 patients). Odesa-region patients most commonly were from Izmail and Bilhorod Dnistrovskyi districts. The worm was more commonly located in the orbital tissue (53 of 58 patients or 91.4%) than in the eyelids (5 patients or 8.6%). All patients complained of skin redness and swollen eyelids. With further migration of the worm deep into the orbital tissue, 15 patients (28.3%) developed exophthalmos of not more than 2-3 mm and 15 patients (28.3%) developed diplopia. The study showed evidence of D. repens infection by parasitological methods of diagnosis in all the 58 study patients, with a mature female found in 44 patients (75.9%), mature female remnants in 11 patients (19.0%), an immature female in 2 patients (3.4%), and a male in one patient (1.8%). The worms were elongated, less than or equal to 1.0-mm thick and 2.2-15 mm in length. Conclusion: First, worm extraction surgery is an essential treatment for ocular dirofilariasis (irrespective whether the worm is located in the eyelid, orbit or eye) and must be accompanied by disinfectant, anti-inflammatory and antihistamine therapy, both topical (eyedrops and ointments) and oral. Second, an ultrasound of the orbital tissue and eyelids may become a gold standard (along with CT and MRI) for the differential diagnosis of dirofilariasis.